La mujer sacralizada: la presencia de las mujeres en los santuarios (lectura desde los exvotos de bronce iberos) - Rueda Galán, Carmen (Complutum, 2007)
The study of the Iberian sanctuaries and of the bronze exvotes is a fundamental area for the analysis of Iberian women. Along with the sculpture, paintings and other art works, the bronze exvotes are the widest range of images of the Iberian society. This paper shows several gender interpretations of exvotes classified by ritual criteria.